Retrato del artista James Joyce, adolescente (2010)
ABSTRACT: The contrast between some lessons in Seminar XXIII of Jacques Lacan with A Portrait of the Artist as a Young Man by James Joyce, that was one of Lacan's sources, brings about how the work depicts Joyce as a young man, finding the knottings where the foreclosure of the Name of the Father did not allow him to respond and could lead to some 1 Analista practicante en Medellín. Profesor en el Departamento de Psicoanálisis de la Universidad de Antioquia. Miembro de la Asociación Mundial de Psicoanálisis y de la detachments that would trigger his psychosis. Nevertheless, with his work he was gradually building a work that was useful as Sinthome and knotting of his structure.